Lumberjanes. Volume 7, A bird's-eye view - Watters, Shannon; Leyh, Kat (Boom! Box, 2017)
The High Council is coming to camp, so Counselor Jen wants to make sure everything is perfect--however, a storm is brewing, and then kittens from the boys' camp seem to develop magic powers.